Characterizing variability of in vivo Raman spectroscopic properties of different anatomical sites of normal colorectal tissue towards cancer diagnosis at colonoscopy - Bergholt, Mads Sylvest Ylvest (American Chemical Society, 2016)
10.1021/ac503287u